PERILAKU KONSUMTIF K-POP FANS BERDASARKAN TEORI KONSUMSI AL GHAZALI - Madaniya, Nadiya El (Jurnal Istiqro, 2024)
The Korean wave phenomenon is currently loved worldwide, and teenagers in Indonesia are no exception. So that it causes the level of consumption of k-pop fans to increase, where they cannot distinguish between what is a mere need and want. In Islam, consumption must comply with Islamic law to avoid things prohibited by law. This study aims to find out how the consumption behaviour of k-pop fans is based on al-Ghazali's consumption theory. This study uses a qualitative method with a phenomenological approach, the data collected is in the form of information, comments, opinions or suggestions about the phenomenon of the consumptive behaviour of k-pop fans. The objects studied were respondents who are k-pop fans on social media, and interviews with the closest people who are k-pop fans. The study results show that the consumption behaviour of k-pop fans is not in accordance with al-Ghazali's consumption theory, in which they buy or consume only for desire and satisfaction without regard to needs. Most fans spend their wealth too much without seeing the benefits and functions of these items. But in fact, there is no prohibition if the needs of hajiyyat and dharuriyyat have been met, and there is no element of coercion in buying these goods.